2016
DOI: 10.1002/jbmr.2908
|View full text |Cite
|
Sign up to set email alerts
|

FAK Promotes Osteoblast Progenitor Cell Proliferation and Differentiation by Enhancing Wnt Signaling

Abstract: Decreased bone formation is often associated with increased bone marrow adiposity. The molecular mechanisms that are accountable for the negative correlation between bone mass and bone marrow adiposity are incompletely understood. Focal adhesion kinase (FAK) has critical functions in proliferation and differentiation of many cell types; however, its roles in osteoblast lineage cells are largely unknown. We show herein that mice lacking FAK in Osterix-expressing cells exhibited decreased osteoblast number and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 42 publications
10
63
0
Order By: Relevance
“…It has been demonstrated that core‐binding factor subunit beta controls the balance between osteoblast and adipocyte lineage through promoting Wnt/β‐catenin signaling . Similarly, we showed that focal adhesion kinase inhibits the adipogenic differentiation potential and enhances the osteogenic differentiation potential of BMSCs through enhancing β‐catenin signaling …”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…It has been demonstrated that core‐binding factor subunit beta controls the balance between osteoblast and adipocyte lineage through promoting Wnt/β‐catenin signaling . Similarly, we showed that focal adhesion kinase inhibits the adipogenic differentiation potential and enhances the osteogenic differentiation potential of BMSCs through enhancing β‐catenin signaling …”
Section: Introductionsupporting
confidence: 52%
“…Male Tsc1 F/F , Osx‐Cre, CHet, and CKO mice were euthanized at the age of 1 month ( n = 9 for each group). Femurs were analyzed by micro–computed tomography (μCT) as reported . In brief, the trabecular region of interest (ROI) from the distal femora was identified as 10% of the bone length starting at the interface between the growth plate and metaphyseal trabecular bone extending into the metaphysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations